THE ROLE OF THE HOSPITAL REGISTRY TO ASSESS THE QUALITY OF STROKE DIAGNOSIS - Moskovko, S.P.; Fiks, D.O.; Shayuk, A.V.; Datsenko, G.V.; Babych, L.V. (World of Medicine and Biology, 2020)
The analysis of the data of the hospital register of stroke, which was performed in Vinnytsia during 2017-2019 in two hospitals according to a unified program have done. The main indicators that characterize the effectiveness of the existing in the region of the diagnostic system for stroke are proposed. The structure, quality indicators of the organization of diagnostic activities (application of stroke scales, timeliness and the fact of neuroimaging, dysphagia screening, consultation with a speech therapist, physiotherapist) were studied and evaluated on a large statistical material.